Pencegahan Stunting dengan Memanfaatkan Garam Beryodium Ud. Sumber Rejeki Di Desa Pajurangan, Kecamatan Gending Kabupaten Probolinggo - Tri Prihatiningsih (Abdi Panca Marga, 2019)
Pajurangi Village is one of the 13 villages in Gending District, Probolinggo Regency. Pajurangi Village is an area close to the beach 250m above sea level, administratively, this village consists of 7 hamlets, 9 RW and 12 RT. The population of this village is approximately 6,987 people with an area of ​​363,363 km2. This village is located in the middle of Probolinggo Regency. One of the village's local potentials is the UMKM UD. Sumber Rejeki which produces iodized salt. Iodized salt is salt that has been enriched with iodine which is needed for growth and intelligence. Iodized salt has a fixed dose to be consumed in accordance with 2019 Ministry of Health standards. Iodine intake can be obtained by consuming iodized salt which is added to dishes or drinks. The use of iodized salt in accordance with the standard can help prevent the occurrence of stunting abnormal growth of children. With the production of iodized salt at UD. Sources of Sustenance can help overcome early stunting and can provide opportunities for unemployment in the village of Pajurangi. This MSME can be developed by promoting salt products to the surrounding community with brochure media. Keywords: Stunting, Iodized Salt, Local Potential